1996
DOI: 10.3382/ps.0750342
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses in Chickens Against Lipopolysaccharide of Escherichia coli and Salmonella typhimurium

Abstract: Immunization of chickens with whole bacteria results in the production of antibodies specific to lipopolysaccharide (LPS), a major constituent of the outer membrane of Gram-negative bacteria. However, there is relatively limited information available concerning immune response of purified LPS in this species. In the present study, immune responses were examined in serum and egg yolk from two groups of chickens injected with entire LPS from Escherichia coli and lipid A free LPS from Salmonella typhimurium. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 16 publications
5
45
0
Order By: Relevance
“…These results indicated that bovine decorin is highly antigenic to chickens. The total IgY concentrations monitored in the egg yolk from the three chickens during the experimental period were found to be relatively constant (9.8 ± 1.5 mg mL -1 , P > 0.05) as reported previously (Sunwoo et al 1996).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…These results indicated that bovine decorin is highly antigenic to chickens. The total IgY concentrations monitored in the egg yolk from the three chickens during the experimental period were found to be relatively constant (9.8 ± 1.5 mg mL -1 , P > 0.05) as reported previously (Sunwoo et al 1996).…”
Section: Resultssupporting
confidence: 56%
“…Radial immunodiffusion of WSF was performed by the method previously described by Sunwoo et al (1996). Solution A was prepared by mixing 1.2 mL rabbit antichicken IgG with 6.8 mL barbital buffer (50 mM sodium barbital and 10 mM barbital, pH 8.6) and incubating in a 56°C water bath.…”
Section: Radial Immunodiffusionmentioning
confidence: 99%
“…To confirm that gallinacins participate in the defense against pathogens, it is necessary to examine whether their expression is enhanced in response to microorganisms or their components. Lipopolysaccharide (LPS) is the major cell wall constituent of Gram-negative bacteria such as Escherichia coli and Salmonella (Morrison & Ryan 1987) and can be used to mimic bacterial infections and inflammation (Sunwoo et al 1996, Leshchinsky & Klasing 2003. The goal of this study was to determine the types of gallinacins that play a role in the elimination of pathogens in the follicles of laying hens, specifically, which types of GALs are expressed in ovarian follicles and whether their expression changes with follicular growth in healthy birds.…”
Section: Introductionmentioning
confidence: 99%
“…LPS also mimics the effects of antigenic exposure in the wild because it is derived from pathogens that induce illness in natural populations. More importantly, in birds it elicits an antibody response by the immunized individual and these antibodies are transmitted to egg yolks (Sunwoo et al, 1996). Avian reovirus is a viral infection that affects captive poultry, as well as wild populations of Galliformes (Magee et al, 1993;Jones, 2000).…”
Section: Introductionmentioning
confidence: 99%